Localized Global Economies on the Northern Borderlands of Mexico and Morocco - Trinidad Requena, Antonio; Soriano-Miras, Rosa M.; Solís, Marlene; Kopinak, Kathryn (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This comparative study examines the processes of development and the configurations of export industries in northern Morocco and on the northern border of Mexico. As the contributors explore the similar characteristics of these two borders, they also examine how the global economy circulates around "places of production"-sites advantageous to the development of export industries. Focusing on transnational firms and the working conditions, settlement processes, and migratory flows they engender, this volume considers if a convergence toward a global culture is inevitable in places of production, or if local resistance emerges in response to the impact of the global.